Influence of race distance and biological sex on age-related declines in triathlon performance: Part A - Wu, S. S. X. (Journal of Science and Cycling, 2013)
This study examined the effect of biological sex and race distance on the age-related declines in swimming, cycling, running and overall performances of the sprint, Olympic, Half-Ironman and Ironman triathlons. Individual discipline and overall performance time of the top 20% non-elite males (n=468) and females (n=146) were compared by categorizing into four 10-year age-groups (20-29, 30-39, 40-49, 50+ years) and normalising to the mean performance time of the fastest age-group for each race. An earlier, larger and faster rate of decline (p=0.01) in performance with ageing was observed in females (=30 years, 9.3%, 3.0% per decade respectively) and males (=40 years, 5.9%, 2.2% per decade, respectively) for the longer events (half-Ironman and Ironman) compared with the shorter distances (sprint and Olympic, =50 years for both sexes). A greater magnitude of decline was observed in swimming for both sexes, especially in the longer events, when compared with cycling and running (12.8%, 5.6%, 9.3% for females, 9.4%, 3.7%, 7.3% for males, in the swim, cycle and run disciplines, respectively). These results indicate that both race distance and biological sex influence the age-related decline in triathlon performance and could aid athletes in optimising training programs to attenuate the age-related declines in performance across different disciplines and distances. Specifically, older athletes may benefit from greater emphasis on swim training and factors that may influence performance during longer distance triathlons.